Meta-analysis of functional neuroimaging and dispositional variables for clinical empathy. (November 2022) - Chen, Chenyi; Chen, Yu-Hsin; Cheng, Yawei
Abstract: Clinical empathy refers to the ability of healthcare providers (HP) to recognize and understand what patients feel. While neuroimaging investigations have identified a neural network of empathy, activation consistency of brain regions and their specific functions in clinical empathy remains unclear. Herein, we conducted meta-analyses of dispositional assessments using random-effects models and functional neuroimaging using Seed-based d Mapping with Permutation of Subject Images to ascertain the shared neural processes consistently identified as relevant to clinical empathy. The dispositional meta-analysis (n = 15) revealed that HP exhibited higher scores on empathic concern and perspective taking. The HP neuroimaging meta-analysis (n = 11) identified consistent activation of the anterior mid-cingulate cortex, anterior insula, and ventrolateral prefrontal cortex (vlPFC) while HP vs. controls comparison (n = 9) did not yield robust alterations. The vlPFC mediated positive and negative functional connectivity of the insula. We revisited the framework of emotion regulation in clinical empathy. The empathetic agent flexibly shifts between affective regulatory strategies to meet contextual demands, with vlPFC figuring as the key region where this neural mechanism takes place. Highlights: Meta-analysis of dispositional and fMRI studies exploring clinical empathy in healthcare providers (HP). Healthcare providers exhibited higher scores on empathic concern and perspective-taking. HP showed consistent activation in the anterior mid-cingulate cortex, anterior insula, and ventrolateral prefrontal cortex. The PFC mediated up- and down-regulation of the insula in the neural circuit. Cognitive up- and down-regulation represent a switch between affective engagement and detachment.